(untitled) (Bangladesh Veterinarian, 2024)
The aim of this study was to determine the prevalence of diseases and its associated risk factors in crossbred Friesian calves in a dairy farm in Bangladesh. Date of birth, birth weight, age and sex of 194 calves up to three months old, season of disease occurrence, date of illness and the percentage of IgG in colostrum were recorded. The prevalence of calf diseases was 33.5%, of which 30.1% were suffering from medical conditions, 19.6% having enteritis: only 5% had surgical disorders. Calves up to 21 days old had significantly higher disease prevalence (22.2%) than calves aged 22-90 days (11.3%). The prevalence of diseases was significantly higher (43.1%) in calves with birth weight up to 29 kg than calves with birth weight 30 kg or more (28.7%). The prevalence of diseases was higher in male calves (38.0%) than female (28.7%). The prevalence of diseases was significantly higher (72.4%) in calves consumed colostrum containing 22-24% IgG compared to calves given colostrum containing 28-30% IgG. The prevalence of diseases was significantly higher in rainy season (64.2%) than in summer (29.5%) and in winter (6.1%). Bang. vet. 2023. Vol. 40, No. 1 – 2, 37 – 45